Geomicrobiology of Aquifers in Enugu - Ozoko, Daniel Chukwuemeka; Ezeugwu, Innocent Onyebuchi (European Journal of Applied Sciences, 2025)
This study was undertaken to examine the microbiological and biochemical characteristics of water and sediment samples collected from different locations in Enugu metropolis with a view to determining their quality and possible effects on water chemistry. Ten geographical sites, viz: Emene, New Artisan, Gariki, Trans-Ekulu, Amechi, Centenary, etc. five samples were collected from each geographical site and handled according to standard microbiological procedures, serial dilution, preparation of selective media for the isolation of bacteria and characterization of bacterial isolates. Biochemical tests which includes Gram stain, catalase, coagulase, indole, oxidase, citrate, and sugar fermentation were carried out for isolates characterization. The remarkable outcome was the differences of bacterial isolates across the sites sampled. Microbiological activity involved counts of bacterial populations that were involved in biogeochemical cycling, such as Desulfomicrobium, Geobacter sp., Shewanella sp., Bacillus sp., and Pseudomonas sp. The existence of extensive variability of microbial density across sites was reflected by the results, with Geobacter sp. predominance at Agbani Road (2.5 × 10³ CFU/mL) and Centenary (1.3 × 10⁴ CFU/mL) and suggested active iron reduction. Shewanella sp., which has long been known to be metal-reducing, is highly present in Gariki (2.3 × 10³ CFU/mL) and Agbani Road (2.4 × 10³ CFU/mL), indicating potential redox conversions. Desulfomicrobium, the sulfate-reducing bacterium, is most present in Emene (1.4 × 10³ CFU/mL) and Ologo (2.1 × 10² CFU/mL), indicating potential reduction of sulfate and hydrogen sulfide production. Pseudomonas sp., being a metabolically flexible bacterium, exhibited moderate growth in Ugwuaji (1.6 × 10² CFU/mL) and Amechi (1.1 × 10² CFU/mL), which is indicative of its organic degradation role. Microbial patterns of distribution attest to active microbial-driven processes in the aquifers that control iron, sulfur, and carbon cycling. The results highlight the need for frequent microbial monitoring in order to determine groundwater quality and possible biogeochemical changes.